The Influence of Pre-Competitive Anxiety and Self-Confidence on Dancesport Performance - Sara Aliberti; Gaetano Raiola; Francesca D'Elia; Domenico Cherubini (MDPI AG, 2024)
Competitive dancesport (DS) performance is a multifactorial phenomenon influenced by physical and mental factors. The emotions experienced by athletes in competition are strongly linked to their sports performance. However, to our knowledge, no studies have investigated the direct relationship between performance and emotional states in DS. Consequently, the aims were four: (I) to investigate the influence of anxiety and self-confidence on DS performance; (II) to examine the influence of years of experience, prior victories, and perceived preparedness on performance outcomes; (III) to identify the optimal emotional state levels for peak performance; (IV) to investigate differences between different athletes' levels and class. The participants were 71 Italian DS athletes divided into three groups (22 B-class, 25 C-class, 24 D-class). Before competition, they supplied demographic information about their gender, years of experience, perceived preparedness, previous winnings in the current class, followed by the completion of the Italian version of Revised Competitive State Anxiety Inventory-2 (CSAI-2R). To assess the athletes' performance, the final classification of the competition was taken into consideration. The results showed that both overall and relative variables from the CSAI-2R significantly predicted performance outcomes (p < 0.05), although somatic anxiety did so to a lesser extent. Significant differences emerged between athletes of different classes in terms of years of experience (p = 0.000), perceived preparedness (p = 0.000), cognitive anxiety (p = 0.000) and self-confidence (p = 0.000). The optimal levels for good performance were cognitive anxiety (11.61 ± 2.27), somatic anxiety (15.77 ± 1.72) and self-confidence (15.12 ± 2.56). The findings of this study provide valuable insights into the multifactorial nature of competitive DS performance, particularly highlighting the significant role of emotional states such as anxiety and self-confidence, as well as other variables such as class, level, years of experience and perceived preparedness.